Perancangan Brand Identity dan Media Promosi Jati Garment Sebagai Upaya meningkatkan Brand Awareness - Susanto, Hari (Jurnal Art Nouveau, 2018)
Abstract: Jati Garment is a leading textile company in Sidoarjo. Jati Garment has a variety of textile materials that have unique packaging in each material. When Jati Garment is researched, Jati Garment only has one promotional media to support the promotion of the company. Jati Garment has a good potential level in Sidoarjo therefore researchers want to reintroduce Jati Garment to the public. Researchers use a media promotion design approach to introduce Jati Garment to the public because it is considered as a mass media whose influence can be directly felt then the media campaign used by researchers include corporate identity, merchandise, website. The selection of such promotional media refers to STP analysis related to the market. Researchers hope from alternative solutions designed by researchers to make Jati Garment a company that will be remembered by the community.